Bhinneka Tunggal Ika: Its Norming and Actualization in Democracy in Indonesia - Riyanto, Slamet; Febrian, Febrian; Zanibar, Zen (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Indonesia is a democratic country that has diversity where the people consist of various ethnicities or ethnic groups, races, cultures and languages, as well as religious diversity and political ideologies. Bhinneka Tunggal Ika is the right motto for the Indonesian people who have diversity but want unity. Therefore, it is necessary to normalize Bhinneka Tunggal Ika and actualize it in the implementation of democracy.Purposes of the Research: Analyze and study in depth, as well as find and build legal arguments about how the norming of Bhinneka Tunggal Ika should be in laws and regulations, and how the actualization of the motto of Bhinneka Tunggal Ika should be in the implementation of democracy in Indonesia. Furthermore, it can provide appropriate recommendations to related parties.Methods of the Research: This normative legal research uses research sources in the form of legal sources and literature studies. The approaches used are: statute approach, conceptual approach, historical approach, comparative approach and futuristic approach. Drawing conclusions in this study by building legal arguments to answer legal issues that have been formulated as research objects.Results of the Research: The results of the discussion are as follows: 1) The standardization of the motto Bhinneka Tunggal Ika is in the 1945 Constitution of the Republic of Indonesia in Article 36A and in Law Number 24 Year 2009, where the regulation becomes a single entity in the State Emblem. 2) Bhinneka Tunggal Ika should be a guideline for the life of the state, and be actualized in democracy through political consensus and deliberation which are the hallmarks of Indonesian democracy.